Spatial distribution of cold-adapted Synechococcus during spring in seas adjacent to Korea - Choi, Dong Han; Noh, Jae Hoon; An, Sung Min; Choi, Yu Ri; Lee, Howon; Ra, Kongtae; Kim, Dongseon; Rho, TaeKeun; Lee, Sang Heon; Kim, Kyung-Tae; Chang, Kyung-Il; Lee, Jung Ho (Algae (Korean Phycological Society), 2016)
We examined the genetic diversity and abundance of picocyanobacteria using barcoded amplicon sequencing approaches and flow cytometry in the East Sea and the East China Sea to determine the distribution patterns of diversity during spring in seas adjacent to the Korean Peninsula. Synechococcus clades I and IV, which have been known as coldadapted ecotypes, dominated at most stations. However, the relative abundances of the two dominant clades differed in their spatial patterns. Clade I was exclusively dominant in the shelf area of the East China Sea and the north East Sea. However, the dominant genotypes belonging to clade I had different spatial distributions in the two areas and responded oppositely to seawater temperature. The dominance of distinct genotypes under the different ecological conditions suggests the presence of ecologically different ecotypes within the clade. Abundances of clade IV were greater than those of clade I at most stations in the southwest East Sea, showing an apparently different pattern from that of the other areas. A warm-water adapted clade II was observed at significant levels only at stations located in the eastern East China Sea affected by a branch of the warm Kuroshio Current. These results suggest that the physicochemical properties of influencing water masses play an important role in determining the distribution of Synechococcus genotypes.